Analisis Kritis Pendapat Masjfuk Zuhdi tentang Sterilisasi pada Program Keluarga Berencana - Akhmad Farid Mawardi Sufyan; Herlina Utami (Fakultas Syariah IAIN Madura, 2022)
In implementing the family planning program (KB), there are several methods, but the most interesting is the study of sterilization methods. The MUI has issued a fatwa on sterilization 4 times, of which the fourth fatwa is that sterilization is haram except for the last fatwa which is haram with exceptions or conditions. The fatwa was criticized by Masjfuk Zuhdi who argued that the MUI fatwa needed to be reviewed. This research revolves around the focus of the study, what is Masjfuk Zuhdi's opinion about sterilization in the family planning program and what is the analysis of Masjfuk Zuhdi's opinion about sterilization in the family planning program. This research is a library research. The results of this research show that although the rules of fiqh can be used as a postulate as a factor in changing the new 'illat from the law of sterilization which was originally haram to become permissible due to evidence of recanalization, the success of recanalization in reconnecting the cut channels. has not been proven to be real. Consequently, his opinion about the unlawfulness of sterilization has not been proven in the field.